Roots of the Resurrection Plant Tripogon loliiformis Survive Desiccation Without the Activation of Autophagy Pathways by Maintaining Energy Reserves - Asami, Pauline; Rupasinghe, Thusitha; Moghaddam, Lalehvash; Njaci, Isaac; Roessner, Ute; Mundree, Sagadevan; Williams, Brett (Frontiers in Plant Science, 2019)
Being sessile, plants must regulate energy balance, potentially via source-sink relations, to compromise between growth and survival in harmful conditions. Crops are sensitive, possibly because they allocate their energy resources towards growth and yield rather than stress tolerance. In contrast, resurrection plants tightly regulate sugar metabolism and use a series of physiological adaptations to suppress cell death in their vegetative tissue to regain full metabolic capacity from a desiccated state within 72 hours of watering. Previously, we showed that shoots of the resurrection plant Tripogon loliiformis, initiate autophagy upon dehydration as one strategy to reinstate homeostasis and suppress cell death. Here we describe the relationship between energy status, sugar metabolism, trehalose-mediated activation of autophagy pathways and investigate whether shoots and roots utilise similar desiccation tolerance strategies. We show that despite containing higher levels of trehalose, dehydrated Tripogon roots do not display elevated activation of autophagy pathways. Using targeted and non-targeted metabolomics, Transmission Electron Microscopy (TEM) and transcriptomics we show that T.loliiformis engages a strategy similar to the long-term drought responses of sensitive plants and continues to use the roots as a sink even during sustained stress. Dehydrating T.loliiformis roots contained more sucrose and trehalose-6-phosphate compared to shoots containing an equivalent water content. The increased resources in the roots provides sufficient energy capacity to cope with the stress and thus the activation of autophagy pathways is not required. These results were confirmed by the absence of autophagy in roots by TEM. Upregulation of sweet genes in both shoots and roots show the translocation of sucrose from leaves to roots and within the roots. Differences in the cell’s metabolic status causes starkly different cell death responses between shoots and roots. These findings show how shoots and roots utilise different stress response strategies and may provide candidate targets that can be used as tools for the improvement of stress tolerance in crops.